Prediction of strong topological insulator phase in kagome metal RV6Ge6 - Ahsan, Taosif (2024)
The kagome lattice (comprising geometrically frustrated corner-sharing triangles), historically used in basket weaving and religious rituals, has emerged as an exciting platform for studying exotic phases of matter in quantum physics, such as quantum spin liquids, Chern magnetism, chiral charge density waves, and topological superconductivity. Despite the immense interest in kagome compounds, the exploration of strong topological insulators within this lattice has been scarce. In this work, we propose a new family of kagome compounds, RV6Ge6 (R = rare-earth atom), to host such a strong topological insulator phase. This phase is characterized by backscattering resilient surface states protected by the bulk insulating gap developed due to band inversions. The topological invariants of the band structure in Hilbert space allow us to identify different classes of gapped band structures and confirm the existence of a Z2 topological invariant for bands near the Fermi energy in RV6Ge6 through ab initio calculations. Our investigation establishes RV6Ge6 as a strong topological insulator family among kagome compounds, further expanding the topological possibilities in this exotic lattice geometry. Notably, the electronic structure near the Fermi energy is dominated by the vanadium kagome lattice plane, presenting an exciting opportunity to study kagome physics in isolation from trivial bands. Furthermore, the observation of the topological insulator phase in RV6Ge6, where the vanadium valence state is in the d orbital, creates an unprecedented opportunity to introduce long-range magnetic order within the topological state via doping in the vanadium site and introducing unpaired d-electrons.